2015
DOI: 10.3109/10428194.2014.938327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular epidemiology of neonatal leukemia in Brazil

Abstract: The clinical and molecular findings of 77 cases of neonatal leukemia (NL) and 380 of infant leukemia (IL) were selected to distinguish features between NL and IL. Somatic gene mutations associated with acute leukemia including FLT3, RAS and PTPN11 were revisited. There were 42 cases of congenital leukemia associated with Down syndrome (DS) and 39 of these cases presented features of acute myeloid leukemia (AML)-M7. Twenty-seven of the DS cases underwent spontaneous remission and were reclassified as a transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Accurate estimates are lacking, however, as most reports of leukaemia incidence in neonates also includes infants and/or older children. Retrospective studies in the Netherlands and Brazil suggest that neonatal leukaemia accounts for <1% of all childhood leukaemia (Bresters et al , ; Moura et al , ). In the Netherlands study (Bresters et al , ), the authors identified 15 cases during the 25‐year study period from 1975 to 1999 (i.e.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate estimates are lacking, however, as most reports of leukaemia incidence in neonates also includes infants and/or older children. Retrospective studies in the Netherlands and Brazil suggest that neonatal leukaemia accounts for <1% of all childhood leukaemia (Bresters et al , ; Moura et al , ). In the Netherlands study (Bresters et al , ), the authors identified 15 cases during the 25‐year study period from 1975 to 1999 (i.e.…”
Section: Epidemiologymentioning
confidence: 99%
“…less than 1 case per year) compared to 122 children with leukaemia aged 0–14 years in a single year (1999). The study from Brazil identified 35 cases of non‐DS leukaemia in neonates, also over a 25‐year period (1990–2013) compared to 404 cases of leukaemia in all children under the age of 12 months over the same time period (Moura et al , ). A widely quoted study from almost 40 years ago reported an annual incidence of leukaemia in children diagnosed in the first year of life as 31·8 per million live births (Bader & Miller, ).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Prematurity, diaper rash, poor hygiene, trauma, anorectal diseases, urethral catheterization, circumcision, insect bite, strangulated hernia, omphalitis, systemic infections, immunocompromised status and hematologic malignancies are some predisposing factors in children ( 1 , 4 , 5 ). Congenital leukemia defined as leukemia diagnosed in the first 28 days of life, is quite rare with an incidence of 4.7 cases per million births ( 6 , 7 ). The prevalence of acute myeloid leukemia (AML) is more than acute lymphoblastic leukemia (ALL) in neonates, with acute myelomonocytic (M4) and monocytic (M5) being the most common subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, approximately 10% of i-AML has myelodysplastic syndrome with monosomy 7 or del(7q), has Down Syndrome (DS), has Noonan syndrome or carry neurofibromatosis type 1 mutations, which all predispose to early AML [ 12 , 13 ]. Children with DS have an increased risk of developing leukaemia, and among neonates and infants, AML is associated with GATA-1 recurrent mutations [ 14 16 ]. GATA-1 gene encodes a transcription factor and the mutation results in a truncated form of the protein GATA-1 that in physiological haematopoiesis interacts with other myeloid-lineage regulator genes.…”
Section: The Profile Of Genomic Aberrations Found In Early-age Amlmentioning
confidence: 99%